Bioactive glass-based fibrous wound dressings - Homaeigohar, Shahin; Li, Meng; Boccaccini, Aldo R. (Burns & Trauma, 2022)
Since the discovery of silicate bioactive glass (BG) by Larry Hench in 1969, different classes of BGs have been researched over decades mainly for bone regeneration. More recently, validating the beneficial influence of BGs with tailored compositions on angiogenesis, immunogenicity and bacterial infection, the applicability of BGs has been extended to soft tissue repair and wound healing. Particularly, fibrous wound dressings comprising BG particle reinforced polymer nanofibers and cotton-candy-like BG fibers have been proven to be successful for wound healing applications. Such fibrous dressing materials imitate the physical structure of skin's extracellular matrix and release biologically active ions e.g. regenerative, pro-angiogenic and antibacterial ions, e.g. borate, copper, zinc, etc., that can provoke cellular activities to regenerate the lost skin tissue and to induce new vessels formation, while keeping an anti-infection environment. In the current review, we discuss different BG fibrous materials meant for wound healing applications and cover the relevant literature in the past decade. The production methods for BG-containing fibers are explained and as fibrous wound dressing materials, their wound healing and bactericidal mechanisms, depending on the ions they release, are discussed. The present gaps in this research area are highlighted and new strategies to address them are suggested.
CRIS-Team WoS Importer:2022-10-21

Cross-linking of mesoporous bioactive glass nanoparticle incorporated gelatin hydrogels by tannic acid with enhanced mechanical performance and stability - Chen, Si; Li, Meng; Michálek, Martin; Kaňková, Hana; Zhao, Liang; Boccaccini, Aldo R.; Galusek, Dušan; Zheng, Kai (Materialia, 2024)
Gelatin-based hydrogels are used in diverse biomedical applications, such as wound dressings, tissue regeneration, and cell culture models. However, gelatin requires additional cross-linking to form a stable hydrogel. Tannic acid (TA), a polyphenolic compound, can undergo the Michael addition reaction and Schiff's base reaction with primary amine groups in neutral aqueous solutions. In this work, TA was selected as a cross-linker of gelatin to fabricate hydrogels reacting with primary amine groups in the gelatin molecular chain. Primary amine-modified mesoporous bioactive glass nanoparticles (AMBGNs) were added to further enhance the cross-linking of the system. The swelling ratios and weight losses showed that the most stable hydrogels retain approximately 53 % of their mass after 28 days of immersion in PBS solution. Young's modulus increased significantly with the increase in the content of TA and AMBGNs. The addition of TA and AMBGNs also resulted in a substantial reduction of gelation time. The prepared hydrogels possessed adequate stability and mechanical properties and showed potential for customized application in a variety of clinical service settings, such as wound healing, bone regeneration, and soft tissue regeneration.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Bioactive glasses; Gelatin; Tannic acid

Electrospinning of recombinant human-like collagen-reinforced PCL nanofibrous membranes using benign solvents for periodontal regeneration - Ren, Minyi; Li, Meng; Boccaccini, Aldo R.; Xu, Yan; Li, Lu; Zheng, Kai (International Journal of Biological Macromolecules, 2025)
Periodontal tissue defects are a leading cause of tooth loss in adults. Guided tissue regeneration (GTR) has emerged as an effective clinical approach for promoting periodontal regeneration. In this study, we employed a green electrospinning technology to combine recombinant human-like collagen (RHC) with polycaprolactone (PCL) to fabricate RHC/PCL membranes for periodontal regeneration. Our results showed that incorporating RHC into PCL up to 40 wt% did not significantly affect the nanofibrous structure of the PCL membranes. When the RHC concentration exceeded 10 wt%, both the tensile strength and modulus of the PCL membranes increased. Additionally, the presence of RHC improved the hydrophilicity of membranes. Biologically, the addition of RHC, regardless of its concentration, significantly enhanced the adhesion, proliferation, and osteogenic differentiation of human periodontal ligament stem cells (hPDLSCs). These effects were confirmed through various assays, including the CCK-8 assay, live/dead staining, as well as ALP and ARS staining. Further, real-time quantitative PCR and Western blot analysis revealed upregulation of osteogenesis-related genes and proteins. Transcriptome sequencing analysis suggested that the PI3K-Akt signaling pathway might play a critical role in the enhanced osteogenesis induced by RHC. Our results emphasize the potential of RHC/PCL nanofibrous membranes to advance the field of periodontal tissue repair.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Electrospinning; Periodontal regeneration; Recombinant collagen

Strontium and Zinc Co-Doped Mesoporous Bioactive Glass Nanoparticles for Potential Use in Bone Tissue Engineering Applications - Naruphontjirakul, Parichart; Li, Meng; Boccaccini, Aldo R. (Nanomaterials, 2024)
Mesoporous bioactive glass nanoparticles (MBGNs) have attracted significant attention as multifunctional nanocarriers for various applications in both hard and soft tissue engineering. In this study, multifunctional strontium (Sr)- and zinc (Zn)-containing MBGNs were successfully synthesized via the microemulsion-assisted sol–gel method combined with a cationic surfactant (cetyltrimethylammonium bromide, CTAB). Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs exhibited spherical shapes in the nanoscale range of 100 ± 20 nm with a mesoporous structure. Sr and Zn were co-substituted in MBGNs (60SiO2-40CaO) to induce osteogenic potential and antibacterial properties without altering their size, morphology, negative surface charge, amorphous nature, mesoporous structure, and pore size. The synthesized MBGNs facilitated bioactivity by promoting the formation of an apatite-like layer on the surface of the particles after immersion in Simulated Body Fluid (SBF). The effect of the particles on the metabolic activity of human mesenchymal stem cells was concentration-dependent. The hMSCs exposed to Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs at 200 μg/mL enhanced calcium deposition and osteogenic differentiation without osteogenic supplements. Moreover, the cellular uptake and internalization of Sr-MBGNs, Zn-MBGNs, and Sr-Zn-MBGNs in hMSCs were observed. These novel particles, which exhibited multiple functionalities, including promoting bone regeneration, delivering therapeutic ions intracellularly, and inhibiting the growth of Staphylococcus aureus and Escherichia coli, are potential nanocarriers for bone regeneration applications.
CRIS-Team Scopus Importer:2024-04-19
Keywords: antibacterial activity; bioactive glass nanoparticle; bioactivity; intracellular delivery; mesoporous